Islam, the people and the state : political ideas and movement in the middle east - Zubaida, Sami (London : I.B. Tauris, 2010)
"Sam Zubaida unpicks the phenomena which have come to define the Middle East in popular imagination: radical religious movements like the Muslim Brotherhood, authoritarian dynasties like the Sauds, anti-Western demagogues like Iran's Mahmoud Ahmadinegad. He shows that, far from being an expression of the 'essential' character of an 'Islamic' region, they are produced by a series of historical, cultural and economic processes. He highlights the historical, religious and cultural diversity of the region, and argues persuasively against viewing it through the prism of Islam. He shows that movements such as Hezbollah and Hamas are not a rejection of modernity but a part of it. In a new chapter, he probes the 'Islamisation' of the region which is alleged to have taken place in recent years and argues that a superfical increase of religious symbols in public life masks a more fundamental and irreversible process of secularization."--Jacket
Includes bibliographical references and Index.